A reading of the novels of James Courage : a thesis presented in partial fulfilment of the requirements for the degree of Master of Arts in English at Massey University - Harris, Grant Richard (Massey University, 1990)
This thesis examines in detail the eight novels of James Courage (1903- 1963) expatriate New Zealand novelist. The Introduction provides some biographical details of the author's family, his early life in Canterbury province, and his subsequent years in England. The case is made for seeing each of Courage's novels as part of a developing canon of work in which the themes of family relationships and the ongoing struggle for the child to break free of emotional ties with the parents constantly recur and are imaginatively reworked. The relationship between the mother and son is seen to be of particular concern to the author. While some other literary influences are considered, especially that of D.H. Lawrence, the ideas of Sigmund Freud are seen as a major influence on Courage's thinking about primal relationships between parent and child, and about the establishment of sexual orientation. Some possible reasons for Courage's decision to live in England rather than New Zealand are suggested. The attempt is made to justify seeing the author as a "New Zealand" novelist in spite of his expatriate status. In this process of justification the ideas of H.S. Canby and LA, Gordon on the relationship between literature and national identity are also discussed. Courage is claimed to be a New Zealand rather than an English writer on the basis of his birth, his use of New Zealand settings in so many of his novels, the constant reworking of his early experiences in this country and his portrayal of the small but distinctive section of New Zealand society which he knew so well. In as much as Courage does seem to fictionalise his own experience his novels are seen as having a biographical basis, although the extent to which this is so cannot yet be determined until primary sources of biographical information become available. Following the introductory chapter separate chapters are devoted to full discussion of each novel, working in chronological order from the first, One House (1933), to the last, The Visit to Penmorten (1961 ). Salient features of each novel are discussed and illustrated with references to each text: the points considered fall into the two categories of mechanical considerations such as plotting, characterisation, setting, dialogue, symbolism, and so on, and themes. Links between the novels, particularly in the treatment and development of recurrent themes, are highlighted. It is demonstrated that Courage's novels show his ever increasing skill as a novelist and his growing self-confidence in treating of new or controversial themes, as well as the persistence of minor stylistic faults, especially the tendency to use melodramatic or self conscious dialogue in emotionally-charged scenes. The chapter devoted to discussion of A Way of Love focuses on Courage's unique status in New Zealand literature as the author of the first full- length novel to deal with the theme of homosexuality sensitively and realistically. The discussion involves consideration of the critical and bureaucratic reception of this novel in New Zealand at the time of its publication. Discussion of this novel and its successor includes looking at the ways in which James Courage was an innovative novelist. These include his concern in the fiction with the actual process of producing the fiction --a concern which is strikingly post-modern--and his use of detached, ironic black humour. The Conclusion points to areas of James Courage's life and writing in which further study remains to be done. The two Appendices contain useful material, much of it hitherto unpublished, regarding the publication of the novels and circumstances surrounding the "banning" of A Way of Love by the New Zealand authorities in the early nineteen-sixties.
Pages 132-142 – Best copy available.
Keywords: Courage, James 1903-1963; Criticism and interpretation